A systematic investigation on the impact of the level of oxidation at sulfur and the configuration of R/S-sulfoxide on the solid structure. Issue 23 (27th May 2021) - Zhou, Yanan; Ma, Hongzhi; Yang, Zhongxing; Wu, Chengjun; Sun, Tiemin
Abstract : In this work, the two aspects, different oxidation states of sulfur and diastereomeric sulfoxides, were combined to comprehend the role of crystal packing and different weak intermolecular interactions in the solid state. Abstract : The current research on the crystals of sulfides, sulfoxides, and sulfones has either solely studied their different oxidation state or is limited to the study of diastereomeric sulfoxides but rarely combined the two aspects for systematic studies. Moreover, most of the studies have been focused on application or structural confirmation, rather than quantitative studies on their interactions or crystal packing. To contribute to this development, we report the preparation and solid-state characterization of different oxidation state crystals 3–6, which are the key intermediates of penicillin derivatives. The crystal packing in compounds 3–6 is quite different. Significantly, due to the intrinsic chirality of sulfoxides, the crystal packing in S -sulfoxide 4 and R -sulfoxide 5 is double helix and herringbone fashion, respectively. DFT calculation, energy framework, and Hirshfeld surface analysis have been used to get insights into the crystal structure features. As far as we know, such a systematic study has not been reported in the literature to date. The present work contributes to provide a new vision for developing improved penicillin derivatives and offering considerable potential in the context of crystal engineering.